2016
DOI: 10.1155/2016/2508381
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Model of Peripheral Photocoagulation for the Prevention of Progressive Diabetic Capillary Occlusion

Abstract: We developed a computational model of the propagation of retinal ischemia in diabetic retinopathy and analyzed the consequences of various patterns and sizes of burns in peripheral retinal photocoagulation. The model addresses retinal ischemia as a phenomenon of adverse local feedback in which once a capillary is occluded there is an elevated probability of occlusion of adjacent capillaries resulting in enlarging areas of retinal ischemia as is commonly seen clinically. Retinal burns of different sizes and pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…AO retinal imaging is providing an improved ability to precisely characterize capillary velocity and diameter, which together determine blood flow. These measurements hold forth the promise of improved retinal capillary blood flow and shear stress and improved understanding of how they impact the eye (Fu et al, 2016; Gast et al, 2016; Lu et al, 2016b).…”
Section: Ao Based Measurements Of Retinal Functionmentioning
confidence: 99%
“…AO retinal imaging is providing an improved ability to precisely characterize capillary velocity and diameter, which together determine blood flow. These measurements hold forth the promise of improved retinal capillary blood flow and shear stress and improved understanding of how they impact the eye (Fu et al, 2016; Gast et al, 2016; Lu et al, 2016b).…”
Section: Ao Based Measurements Of Retinal Functionmentioning
confidence: 99%
“…While practice has shown the efficiency of the procedure, its mechanisms of action remain unclear. It is thought that the procedure acts by reducing the oxygen consumption of the photoreceptors affected by the laser-induced burn [93,115]. However, effects of the therapy on blood flow have been observed [93].…”
Section: Models Of Drmentioning
confidence: 99%
“…The burn patterns used in panretinal photocoagulation are also subject to debate. Gast et al investigated the effects of different patterns on the propagation of ischaemia due to capillary occlusion [115]. The model showed how different burn patterns affect the propagation of ischaemia and suggested that targeting the non-ischaemic peripheral retina with appropriate patterns may be effective at containing it.…”
Section: Models Of Drmentioning
confidence: 99%
See 1 more Smart Citation
“…In ABMs, the agents are capable of independent decision making according to assigned attributes and conditions [ 22 , 23 ]. Cellular ABMs can introduce tissue heterogeneity to models by their very nature, as cells are individually modeled and can differ from one another, space itself is a model component [ 24 , 25 , 26 , 27 , 28 ]. A recent report on comparative biology immune ABM ( CBIABM ) has presented a model of mechanism-based differences in bat and human immune systems and discusses the consequences of these differences on disease manifestation [ 29 ].…”
Section: Introductionmentioning
confidence: 99%